ENVIRONMENTAL DIPLOMACY: HISTORY AND CURRENT ISSUES - Poda, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
The paper analyzes the history and the stages of the development of environmental diplomacy. Its achievements are summarized and the current state is described. Environmental diplomacy as a phenomenon of the XX-XXI centuries arose as a result of the world community's reaction to the threat of an ecological catastrophe. Environmental diplomacy is a complex and multifaceted phenomenon that develops at several levels: the global level, represented by the functioning of the UN and the activities of the EU; regional level of diplomacy: environmental activities conducted by the regional environmental institutes.